Rural accommodation as a sign of space for consensus: Hospedaria Montanha Beija-Flor Dourado, Morretes (PR-Brazil). Issue 3 (2nd September 2019) - Tricárico, Luciano Torres; Santos Pires, Paulo dos; Conceição Walkowski, Marinês da
ABSTRACT: The objective of this research was to demonstrate that sites of rural accommodation in Brazil can mean spaces for consensus. The Hospedaria Montanha Beija-Flor Dourado (Golden Hummingbird Mountain Lodge) in the rural area of Morretes, a municipality in the eastern portion of the state of Paraná, Brazil, became the object of the research which was based on phenomenological, qualitative, exploratory and descriptive study values. The research used primary and secondary data sources. Primary data, and its analysis, consisted of reading the sites in loco using photographic and architectural survey to read the space and consultation of websites, folders, brochures, and videos about the lodge, which were described in the light of assembly theory based upon the concept of abduction of Peircean semiotics. Results presented the denotation of consensus in rural accommodation environments about meaning spaces for civic initiatives, solutions to social demands, and collaborative arrangements in the Brazilian rural area.